Risk factors for hospitalisation and associated costs among patients with hepatitis A associated with imported pomegranate arils, United States, 2013. (July 2016) - Epson, E.E.; Cronquist, A.; Lamba, K.; Kimura, A.C.; Hassan, R.; Selvage, D.; McNeil, C.S.; Varan, A.K.; Silvaggio, J.L.; Fan, L.; Tong, X.; Spradling, P.R.
Abstract: Objectives: To assess hospitalisation risk factors and economic effects associated with a multistate hepatitis A outbreak in 2013. Study design: Retrospective case series. Methods: Eligible outbreak-related cases confirmed by September 1, 2013, were defined as acute hepatitis symptoms and positive IgM anti-hepatitis A during March 15–August 12 among patients who consumed the food vehicle or had the outbreak genotype. We reviewed medical records, comparing demographic and clinical characteristics among hospitalized and non-hospitalized patients; we used logistic regression analysis to identify factors associated with hospitalization. We interviewed patients regarding symptom duration and healthcare usage and estimated per-patient and total costs. Health departments reported outbreak-related personnel hours. Results: Medical records were reviewed for 147/159 (92%) eligible patients; median age was 48 (range: 1–84) years, and 64 (44%) patients were hospitalized. Having any chronic medical condition was independently associated with hospitalisation (odds ratio, 3.80; 95% confidence interval, 1.68–8.62). Interviews were completed for 114 (72%) eligible patients; estimated per-patient cost of healthcare and productivity loss was $13, 467 for hospitalized and $2138 for non-hospitalized patients and $1, 304, 648 for all 165 outbreak-related cases. State and local public health personnel expenditures included 82 h and $3221/outbreak-related case. Conclusions: Hospitalisations in this outbreak were associated with chronic medical conditions and resulted in substantial healthcare usage and lost productivity. These data can be used to inform future evaluation of expansion of hepatitis A vaccination recommendations to include adults with chronic medical conditions. Highlights: We investigated risk factors for hospitalization during a foodborne hepatitis A outbreak. Hospitalizations were associated with having chronic medical conditions. Hospitalizations resulted in substantial healthcare usage and lost productivity. Our data can inform future evaluation of hepatitis A vaccination recommendations.